Questioning hagfish affinities of the enigmatic Devonian vertebrate Palaeospondylus. Issue 7 (19th July 2017) - Johanson, Zerina; Smith, Moya; Sanchez, Sophie; Senden, Tim; Trinajstic, Kate; Pfaff, Cathrin
Abstract : Palaeospondylus gunni Traquair, 1890 is an enigmatic Devonian vertebrate whose taxonomic affinities have been debated since it was first described. Most recently, Palaeospondylus has been identified as a stem-group hagfish (Myxinoidea). However, one character questioning this assignment is the presence of three semicircular canals in the otic region of the cartilaginous skull, a feature of jawed vertebrates. Additionally, new tomographic data reveal that the following characters of crown-group gnathostomes (chondrichthyans + osteichthyans) are present in Palaeospondylus : a longer telencephalic region of the braincase, separation of otic and occipital regions by the otico-occipital fissure, and vertebral centra. As well, a precerebral fontanelle and postorbital articulation of the palatoquadrate are characteristic of certain chondrichthyans. Similarities in the structure of the postorbital process to taxa such as Pucapampella, and possible presence of the ventral cranial fissure, both support a resolution of Pa. gunni as a stem chondrichthyan. The internally mineralized cartilaginous skeleton in Palaeospondylus may represent a stage in the loss of bone characteristic of the Chondrichthyes.